Supramolecular hydrogel packer constructed by interaction of subject and object as well as preparation method and application of supramolecular hydrogel packer

By using supramolecular hydrogel sealant constructed with host-guest interaction during drilling, the problem of heavy oil invasion into the wellbore is solved, efficient sealing and unsealing is achieved, and complex situations such as annular blockage and drilling are avoided.

CN119899330AActive Publication Date: 2025-04-29CHINA UNIV OF PETROLEUM (EAST CHINA)

Patent Information

Application Number
CN202510399678.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-04-29
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the problem of heavy oil entering the wellbore during drilling, resulting in complex situations such as annex blockage and drilling jams.

Method used

A supramolecular hydrogel sealant constructed by host-guest interaction, consisting of copolymerized monomers, tanninic acid-grafted polysaccharide aqueous dispersion, initiator and crosslinking agent, can form a high-strength, high-pressure sealant at formation temperature and achieve degradation under alkaline conditions.

Benefits of technology

Effectively seal the heavy oil reservoir, reduce heavy oil entering the wellbore, avoid annular blockage and drilling, and at the same time achieve the degradation of the hydrogel, achieving the decapsulation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a supramolecular hydrogel packer constructed by interaction of a subject and an object as well as a preparation method and application of the supramolecular hydrogel packer, and belongs to the technical field of drilling fluid packing. The supramolecular hydrogel packer constructed by interaction of the subject and the guest comprises the following raw materials in percentage by mass: 12-36% of a copolymerization monomer, 6-10% of a tannic acid grafted polysaccharide aqueous dispersion, 0.5-1.5% of an initiator, 0.3-0.6% of a cross-linking agent and the balance of water, the total amount of the components is 100%. The raw materials are cheap, easy to obtain, simple in composition, low in cost, green, safe and environment-friendly; the preparation method is simple, mild in condition and easy to implement. After crosslinking, the obtained packer has excellent mechanical properties, temperature and pressure resistance and outstanding pH degradation capability, and can effectively pack a crude oil reservoir to form an integral sealing interlayer, so that heavy oil entering a shaft is reduced; meanwhile, degradation of the hydrogel can be effectively realized, and deblocking is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a supramolecular hydrogel sealing agent constructed by host-guest interaction and a preparation method and application thereof, belonging to the technical field of drilling fluid sealing. Background Art

[0002] With the continuous growth of global energy demand, the development of conventional oil and gas resources has gradually entered the middle and late stages. The depletion of resources and the increasing difficulty of mining have led to a significant increase in development costs. In this environment, the development of unconventional oil and gas resources (such as heavy oil, shale oil, oil sands, etc.) has become an important supplement to the global energy supply. Among them, as an important type of unconventional oil and gas resources, heavy oil has a global reserve far exceeding conventional crude oil. It is estimated that it accounts for more than 70% of the world's total oil reserves and has huge development potential. However, compared with conventional crude oil, heavy oil has significant characteristics such as high viscosity, high density, and poor fluidity. These characteristics cause heavy oil to face many challenges in the mining process. In particular, when the drill tool drills through the heavy oil reservoir, the pressure difference in the wellbore changes, and the heavy oil is very easy to invade the drilling fluid system. The invading heavy oil will migrate along the wellbore wall, which not only destroys the rheological properties of the drilling fluid, but also significantly increases the risk of downhole complex situations such as annular blockage and stuck pipe. These problems not only lead to extended drilling cycles and increased operating costs, but also pose a serious threat to the safety and efficiency of drilling operations.

[0003] Faced with the severe challenge of heavy oil invading the wellbore, researchers at home and abroad have adopted a series of treatment methods. Such as heavy slurry push, heating to reduce viscosity, adding heavy oil viscosity reducer, adding plugging materials, etc. Among them, heavy slurry push is to balance the pressure difference between the well and the formation by increasing the density of the drilling fluid, but it cannot fundamentally prevent the invasion of heavy oil. Although heating to reduce viscosity can temporarily reduce the viscosity of heavy oil in the wellbore, it has high energy consumption and is difficult to implement in deep wells. Heavy oil viscosity reducer uses chemical means to change the rheological properties of heavy oil. Although it can improve the fluidity of heavy oil, when the amount of heavy oil invading is large, it often cannot achieve the ideal viscosity reduction effect. Although plugging materials can effectively fill cracks, they cannot achieve effective unblocking, resulting in obstruction of subsequent mining operations and affecting subsequent heavy oil production capacity. In summary, these existing methods all have certain limitations and cannot comprehensively and effectively control the problem of heavy oil invasion.

[0004] In recent years, supramolecular polymer gel, as a new type of functional material, has attracted extensive attention in the field of oilfield chemistry due to its unique reversibility and environmental responsiveness. Supramolecular gel forms a dynamic cross-linked network through non-covalent bonds (such as hydrogen bonds, hydrophobic interactions, etc.), which not only has good mechanical properties and adaptability, but also can achieve reversible unblocking under specific conditions, providing a new idea for solving the problem of heavy oil isolation. Chinese patent document CN116120905A discloses a supramolecular polymer gel based on multiple hydrogen bonds, which inhibits the ionization of carboxylic acid groups (-COOH) by adjusting the pH value of the dissolving solution to acidity, thereby providing more active sites for the formation of multiple hydrogen bonds. The gel system uses azo initiators to initiate the polymerization of olefin-containing carboxylic acid group monomers under ultraviolet light to form long polymer chains, and achieves gelation through physical cross-linking. Compared with traditional chemical cross-linked gels, this system does not require a cross-linking agent, avoiding the problem of difficult control of gelation time. At the same time, its viscosity changes with the shear rate, and can automatically adapt to the plugging pumping process, reduce the pumping construction pressure, adapt to the harsh leaking layer pressure environment, and reduce the risk of re-leakage. However, the gel material still has certain limitations, especially the inability to achieve reversible plugging, and it is difficult to effectively unblock after plugging, which limits its application in heavy oil reservoir isolation. Therefore, further optimizing the reversibility of the gel material and achieving an effective balance between heavy oil plugging and unblocking will be an important direction for the future research and development of heavy oil reservoir isolation materials. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a supramolecular hydrogel sealing agent constructed by host-guest interaction, and a preparation method and application thereof. The raw materials of the present invention are cheap and easily available, the raw material composition is simple, the cost is low, and it is green, safe and environmentally friendly. The preparation method is simple, the conditions are mild, and it is easy to implement. The sealing agent obtained by the present invention has excellent mechanical properties, heat and pressure resistance and outstanding pH degradation ability after cross-linking, and can effectively seal the crude oil reservoir to form an integral sealing barrier and reduce the entry of heavy oil into the wellbore; at the same time, it can effectively realize the degradation of the hydrogel to achieve unsealing.

[0006] The technical solution of the present invention is as follows: A supramolecular hydrogel sealing agent constructed by host-guest interaction, comprising the following raw materials in percentage by weight: 12-36% copolymerization monomer, 6-10% tannic acid grafted polysaccharide aqueous dispersion, 0.5-1.5% initiator, 0.3-0.6% crosslinking agent, and the balance being water, wherein the total amount of each component is 100%; The copolymerization monomer is a combination of acryloyl cyclodextrin and a double bond-containing monomer; the double bond-containing monomer is one of acrylamide, acrylic acid, methacrylic acid, sodium acrylate, N-isopropylacrylamide, hexadecyl dimethyl allyl ammonium chloride or N-hydroxyethyl acrylamide; The preparation method of acryloyl cyclodextrin comprises the steps of: dissolving cyclodextrin and sodium hydroxide in deionized water, adding acryloyl chloride or methacryloyl chloride, reacting, filtering, precipitating and drying to obtain acryloyl cyclodextrin; The preparation method of tannic acid grafted polysaccharide aqueous dispersion comprises the following steps: fully dispersing polysaccharide material in deionized water and adjusting the pH to 8.0; adding tannic acid and obtaining tannic acid grafted polysaccharide aqueous dispersion through reaction; the polysaccharide material is one or a combination of two or more of cellulose, starch, lignin, xanthan gum, chitosan, guar gum or sodium alginate.

[0007] Preferably, according to the present invention, the supramolecular hydrogel sealing agent comprises the following raw materials in percentage by mass: 16% copolymerization monomer, 8% tannic acid grafted polysaccharide aqueous dispersion, 1% initiator, 0.4% cross-linking agent, and the balance is water, and the total amount of each component is 100%.

[0008] According to a preferred embodiment of the present invention, in the method for preparing acryloyl cyclodextrin, the cyclodextrin is selected from one or a combination of two or more of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin, preferably β-cyclodextrin.

[0009] Preferably, in the preparation method of acryloyl cyclodextrin according to the present invention, the mass ratio of cyclodextrin to sodium hydroxide is 1-4:5.84, preferably 2:5.84, the mass ratio of cyclodextrin to deionized water is 1:50-150, preferably 1:100, and the mass ratio of acryloyl chloride or methacryloyl chloride to cyclodextrin is 0.5-2.2:2, preferably 1:1.

[0010] Preferably, in the preparation method of acryloyl cyclodextrin according to the present invention, the reaction temperature is 40-60°C, preferably 50°C, the reaction time is 6-12h, preferably 12h, and the reaction is carried out under inert gas protection and stirring conditions. Preferably, the inert gas is nitrogen or argon.

[0011] Preferably, in the preparation method of acryloyl cyclodextrin according to the present invention, the filtrate obtained by filtration is purified by precipitation using acetone, the drying temperature is 40-60° C., preferably 40° C., and the drying time is 12-24 h, preferably 24 h.

[0012] Preferably according to the present invention, the mass ratio of acryloyl cyclodextrin to the double bond-containing monomer is 1:2-8, preferably 1:3.

[0013] Preferably according to the present invention, in the method for preparing the tannic acid grafted polysaccharide aqueous dispersion, the polysaccharide material is cellulose, and the cellulose is selected from nanocellulose fibrils, cellulose nanocrystals or carboxymethyl cellulose.

[0014] Preferably according to the present invention, in the method for preparing the tannic acid grafted polysaccharide aqueous dispersion, the mass ratio of the polysaccharide substance to deionized water is 1:20-30, preferably 1:25.

[0015] Preferably, according to the present invention, in the method for preparing the tannic acid grafted polysaccharide aqueous dispersion, a 0.01 mol / L sodium hydroxide aqueous solution or a 0.01 mol / L HCl aqueous solution is used to adjust the pH to 8.0.

[0016] Preferably, according to the present invention, in the method for preparing the tannic acid-grafted polysaccharide aqueous dispersion, the mass ratio of the polysaccharide substance to the tannic acid is 3:5-8, preferably 3:7.

[0017] Preferably, according to the present invention, in the method for preparing the tannic acid grafted polysaccharide aqueous dispersion, the reaction temperature is room temperature, the reaction time is 12-24 hours, preferably 24 hours; and the reaction is carried out under stirring conditions.

[0018] According to the present invention, in the tannic acid-grafted polysaccharide aqueous dispersion, the tannic acid can form chemical bonds such as hydrogen bonds with the polysaccharide substance, thereby significantly improving the strength and toughness of the polysaccharide substance.

[0019] According to the present invention, the initiator is preferably selected from one or a combination of two or more of azobisisobutyronitrile, azobisisoheptanenitrile, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, potassium persulfate, ammonium persulfate, dicumyl peroxide or di-tert-butyl peroxide, preferably potassium persulfate.

[0020] According to the present invention, the crosslinking agent is preferably selected from one or a combination of two or more of dimethyl sulfide, N,N'-methylenebisacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, ethylene oxide, propylene oxide, phenolic resin, formaldehyde, polyethylene glycol diacrylate or boric acid, preferably N,N'-methylenebisacrylamide.

[0021] The preparation method of the supramolecular hydrogel sealing agent constructed by the host-guest interaction comprises the steps of: fully dispersing copolymerization monomers, tannic acid grafted polysaccharide aqueous dispersion, initiator and crosslinking agent in water at room temperature.

[0022] The application of the supramolecular hydrogel sealing agent constructed by the above host-guest interaction in the crude oil extraction and drilling process.

[0023] According to the preferred embodiment of the present invention, the application method comprises the following steps: during drilling, the supramolecular hydrogel sealing agent is injected into the formation, and gelled at the formation temperature to seal the crude oil reservoir; after the drilling is completed, an alkaline solution is injected to remove the blockage. Preferably, the alkaline solution is a sodium hydroxide aqueous solution with a mass concentration of 5-15%, and the mass ratio of the alkaline solution to the supramolecular hydrogel sealing agent is 30-60:1.

[0024] According to the present invention, during drilling, the dosage and injection method of the supramolecular hydrogel sealing agent can be based on the existing methods; the formation temperature is greater than or equal to 40°C, preferably 40-100°C.

[0025] Preferably according to the present invention, the crude oil is heavy oil, and the heavy oil is crude oil having a viscosity greater than or equal to 1000 mPa·s at 50°C.

[0026] The room temperature in the present invention has a well-known meaning in the art, which refers to 25±5°C.

[0027] The technical features and beneficial effects of the present invention are as follows: (1) The present invention obtains a supramolecular hydrogel sealing agent by compounding copolymerization monomers, tannic acid grafted polysaccharide aqueous dispersion, crosslinking agent, and initiator and dispersing them in water at room temperature. The supramolecular hydrogel sealing agent is in a free-flowing liquid state with suitable viscosity and is easy to pump. After being pumped into the wellbore, copolymerization and crosslinking reactions can be achieved under the reservoir to form a sealing segment plug, and the formation is applicable to a wide temperature range. The sealing segment plug formed by the supramolecular hydrogel has high strength, high pressure bearing capacity, and pH response ability, and can isolate the wellbore to prevent heavy oil from invading the wellbore to cause annular blockage or drill jamming. At the same time, it can be degraded to achieve unsealing.

[0028] (2) At formation temperature, the copolymerization monomers of the present invention are polymerized to form polymers, and the polymers are in situ gelled with the polysaccharides grafted with tannic acid through supramolecular forces, thus obtaining supramolecular hydrogels based on host-guest interactions. Amide groups and other groups in the polymers obtained by polymerization of the copolymerization monomers of the present invention can form hydrogen bonds with phenolic hydroxyl groups, hydroxyl groups and other groups on the polysaccharides grafted with tannic acid. This hydrogen bonding is an important factor in increasing the crosslinking density of the gel, improving mechanical properties and achieving pH degradation. Under alkaline conditions, OH- will attack the phenolic hydroxyl groups of tannic acid, deprotonate it, destroy the hydrogen bonding between tannic acid and β-cyclodextrin, and cause the two to dissociate, and the gel gradually transforms into a sol state.

[0029] (3) Acrylamide polymers can effectively isolate the wellbore and prevent heavy oil from invading the wellbore, causing annular blockage or drill jamming, but the molecular weight of acrylamide polymers is small, and the viscosity and mechanical properties are not ideal. The present invention prepares acryloyl cyclodextrin by reacting acryloyl chloride or methacryloyl chloride with cyclodextrin. The chlorine atoms in acryloyl chloride or methacryloyl chloride replace the hydroxyl groups in cyclodextrin to form ester bonds, introducing a polymerizable double bond structure and improving the stability of the structure. Then, it is copolymerized with double-bond monomers such as acrylamide in the formation to generate a high molecular weight acrylamide-β-cyclodextrin copolymer, which has good properties including retention performance and mechanical properties. The inclusion unit is introduced to include the polysaccharide grafted with tannic acid. Tannic acid can be densely accumulated on the surface of the polysaccharide material in a comb-like form, which is more conducive to the entry of tannic acid into the cavity structure of β-cyclodextrin. The benzene ring of tannic acid can form an inclusion complex in the hydrophobic cavity of β-cyclodextrin, and the phenolic hydroxyl group of tannic acid, the hydroxyl group of the polysaccharide material and the hydroxyl group of β-cyclodextrin form a hydrogen bond structure to form a stable host-guest structure, and form a polysaccharide supramolecular hydrogel with pH degradation ability. The above host-guest structure is stable under acidic and neutral conditions and dissociates under alkaline conditions, thereby achieving pH degradation ability. In the preparation method of acryloyl cyclodextrin of the present invention, the ratio of cyclodextrin and acryloyl chloride or methacryloyl chloride is relatively important, because if the amount of acryloyl chloride or methacryloyl chloride is low, the grafting rate will be reduced.

[0030] (4) The present invention uses tannic acid-grafted polysaccharides as the guest material, which not only reduces environmental pollution, but also increases the elasticity of the gel sealing material, increases the cross-linking density, and improves the mechanical properties, thereby achieving the degradation of the gel under specific conditions. In the preparation method of tannic acid-grafted polysaccharides, the ratio of polysaccharides to tannic acid is particularly important. Among them, when the amount of tannic acid is too high, a large number of tannic acid molecules may accumulate excessively on the surface of the polysaccharide material, which may cause the grafted area to be too thick. There is another situation after the tannic acid is excessive. The interaction force between tannic acid molecules will exceed the interaction force between tannic acid and polysaccharide substances, so that the tannic acid itself aggregates and cannot be evenly grafted on the surface of the polysaccharide substance. When the amount of tannic acid is too low, the surface of the polysaccharide substance cannot be fully grafted.

[0031] (5) The specific types of acryloyl cyclodextrin and double-bond-containing monomers of the present invention are combined with specific ratios and specific tannic acid-grafted polysaccharides, suitable initiators and cross-linking agents to obtain supramolecular hydrogel sealing agents. The supramolecular hydrogel sealing agents obtained by the present invention are gel sealing agents with excellent mechanical properties (high strength, high pressure bearing), temperature resistance and outstanding pH degradation ability, which are formed based on supramolecular interactions (host-guest interactions and hydrogen bond interactions between β-cyclodextrin in the polymer obtained by polymerization of copolymerization monomers and hydroxyl groups in tannic acid-grafted polysaccharides). It not only has the advantages of good matching between gel-type leak-proof plugging materials and wellbores, but also increases the temperature and pressure resistance of gels through supramolecular structure design, has unique pH degradation ability, can effectively seal formation fractures to form an integral sealing barrier, reduce the entry of heavy oil into the wellbore, and can effectively achieve hydrogel degradation and unsealing. The sealing agent of the present invention has heavy oil resistance. In the presence of heavy oil, the sealing agent of the present invention can still gel smoothly at formation temperature, and the obtained gel still maintains high strength and pH degradation ability. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] The raw materials used in the examples are all conventional raw materials and can be obtained commercially; the methods described are all prior art unless otherwise specified.

[0034] Example 1 A nanocellulose supramolecular hydrogel sealing agent comprises the following raw materials in percentage by weight: 4% acryloyl cyclodextrin, 12% acrylamide, 8% tannic acid grafted cellulose aqueous dispersion, 0.4% crosslinking agent (N, N'-methylenebisacrylamide), 1% initiator (potassium persulfate), and the balance water, with the total amount of each component being 100%.

[0035] The acryloyl cyclodextrin is acryloyl β-cyclodextrin, and the preparation method is as follows: β-cyclodextrin and sodium hydroxide are fully dissolved in deionized water, acryloyl chloride is added, and the mixture is stirred and reacted at 50°C for 12 hours under a nitrogen environment. Filter, collect the filtrate, precipitate and purify with acetone, and dry the precipitate in a vacuum oven at 40°C for 24 hours to obtain a pure white solid, which is acryloyl β-cyclodextrin. Among them, the mass ratio of β-cyclodextrin to sodium hydroxide is 2:5.84; the mass ratio of β-cyclodextrin to deionized water is 1:100; and the mass ratio of acryloyl chloride to β-cyclodextrin is 1:1.

[0036] The preparation method of cellulose aqueous dispersion grafted with tannic acid comprises the following steps: fully dispersing nanocellulose fibril gel (available from Nanjing Tianlu Nanotechnology Co., Ltd., with a fiber diameter of 3-5 nm, a fiber length of 500-1000 nm, and a solid content of 2 wt%) in deionized water, adjusting the pH to 8.0 with a sodium hydroxide aqueous solution having a concentration of 0.01 mol / L; adding tannic acid, and reacting at room temperature for 24 hours to obtain a cellulose aqueous dispersion grafted with tannic acid. The mass ratio of nanocellulose fibrils to deionized water is 4:100, and the mass ratio of tannic acid to nanocellulose fibrils is 7:3.

[0037] The preparation method of the nano-cellulose supramolecular hydrogel sealing agent comprises the steps of: fully dispersing acryloyl cyclodextrin, acrylamide, tannic acid grafted cellulose aqueous dispersion, initiator and cross-linking agent in water at room temperature to obtain the nano-cellulose supramolecular hydrogel sealing agent.

[0038] Example 2 A nanocellulose supramolecular hydrogel sealing agent comprises the following raw materials in percentage by weight: 4% acryloyl cyclodextrin, 8% acrylamide, 8% tannic acid grafted cellulose aqueous dispersion, 0.4% crosslinking agent (N, N'-methylenebisacrylamide), 1% initiator (potassium persulfate), and the balance water; the total amount of each component is 100%.

[0039] The preparation method of the cellulose aqueous dispersion grafted with acryloyl cyclodextrin and tannic acid is the same as that in Example 1.

[0040] The preparation method of the above nanocellulose supramolecular hydrogel sealing agent is the same as that in Example 1.

[0041] Example 3 A nanocellulose supramolecular hydrogel sealing agent comprises the following raw materials in percentage by weight: 4% acryloyl cyclodextrin, 12% acrylamide, 8% tannic acid grafted cellulose aqueous dispersion, 0.4% cross-linking agent (polyethylene glycol diacrylate, available from Aladdin, with an average molecular weight of about 600), 1% initiator (potassium persulfate), and the balance water; the total amount of each component is 100%.

[0042] The preparation method of the cellulose aqueous dispersion grafted with acryloyl cyclodextrin and tannic acid is the same as that in Example 1.

[0043] The preparation method of the above nanocellulose supramolecular hydrogel sealing agent is the same as that in Example 1.

[0044] Example 4 A nanocellulose supramolecular hydrogel sealing agent, the raw material composition is the same as that in Example 1, except that: in the preparation of the tannic acid grafted polysaccharide aqueous dispersion, the nanocellulose fibril gel is replaced by a cellulose nanocrystal gel (available from Nanjing Tianlu Nano Technology Co., Ltd., with a fiber diameter of 10-50 nm, a fiber length of 200-500 nm, and a solid content of 8wt%), the mass ratio of cellulose nanocrystals to deionized water is 4:100, and the mass ratio of tannic acid to cellulose nanocrystals is 7:3; other preparation steps and conditions are the same as those in Example 1.

[0045] The preparation method of the above nanocellulose supramolecular hydrogel sealing agent is the same as that in Example 1.

[0046] Example 5 A nanocellulose supramolecular hydrogel sealing agent comprises the following raw materials in percentage by weight: 4% acryloyl cyclodextrin, 32% acrylamide, 8% tannic acid grafted cellulose aqueous dispersion, 0.4% crosslinking agent (N, N'-methylenebisacrylamide), 1% initiator (potassium persulfate), and the balance water; the total amount of each component is 100%.

[0047] The preparation method of the cellulose aqueous dispersion grafted with acryloyl cyclodextrin and tannic acid is the same as that in Example 1.

[0048] The preparation method of the above nanocellulose supramolecular hydrogel sealing agent is the same as that in Example 1.

[0049] Example 6 A nanocellulose supramolecular hydrogel sealing agent comprises the following raw materials in percentage by mass: 4% acryloyl cyclodextrin, 12% acrylamide, 6% tannic acid grafted cellulose aqueous dispersion, 0.3% crosslinking agent (N, N'-methylenebisacrylamide), 0.5% initiator (potassium persulfate), and the balance water; the total amount of each component is 100%.

[0050] The preparation method of the cellulose aqueous dispersion grafted with acryloyl cyclodextrin and tannic acid is the same as that in Example 1.

[0051] The preparation method of the above nanocellulose supramolecular hydrogel sealing agent is the same as that in Example 1.

[0052] Example 7 A nanocellulose supramolecular hydrogel sealing agent comprises the following raw materials in percentage by mass: 4% acryloyl cyclodextrin, 12% acrylamide, 10% tannic acid grafted cellulose aqueous dispersion, 0.6% crosslinking agent (N, N'-methylenebisacrylamide), 1.5% initiator (potassium persulfate), and the balance water; the total amount of each component is 100%.

[0053] The preparation method of the cellulose aqueous dispersion grafted with acryloyl cyclodextrin and tannic acid is the same as that in Example 1.

[0054] The preparation method of the above nanocellulose supramolecular hydrogel sealing agent is the same as that in Example 1.

[0055] Example 8 A nanocellulose supramolecular hydrogel sealing agent, the raw material composition is as described in Example 1, except that acrylamide is replaced by acrylic acid of the same mass.

[0056] The preparation method of the above nanocellulose supramolecular hydrogel sealing agent is the same as that in Example 1.

[0057] Example 9 A nanocellulose supramolecular hydrogel sealing agent, the raw material composition is as described in Example 1, except that in the preparation of acryloyl cyclodextrin, the mass ratio of acryloyl chloride to β-cyclodextrin is 0.5:2, and the other preparation steps and conditions are the same as in Example 1.

[0058] The preparation method of the above nanocellulose supramolecular hydrogel sealing agent is the same as that in Example 1.

[0059] Example 10 A nanocellulose supramolecular hydrogel sealing agent, the raw material composition is as described in Example 1, except that in the preparation of acryloyl cyclodextrin, acryloyl chloride is replaced by methacryloyl chloride of the same mass, and the other preparation steps and conditions are the same as in Example 1.

[0060] The preparation method of the above nanocellulose supramolecular hydrogel sealing agent is the same as that in Example 1.

[0061] Embodiment 11 A nanocellulose supramolecular hydrogel sealing agent, the raw material composition is as described in Example 1, except that in the preparation of the tannic acid grafted polysaccharide aqueous dispersion, the polysaccharide material is lignin, and the other preparation steps and conditions are the same as in Example 1.

[0062] The preparation method of the above nanocellulose supramolecular hydrogel sealing agent is the same as that in Example 1.

[0063] Example 12 A hydrogel sealing agent, the raw material composition is as described in Example 1, except that in the preparation of the tannic acid grafted polysaccharide aqueous dispersion, the mass ratio of tannic acid to nanocellulose fibrils is 5:3, and the other preparation steps and conditions are the same as in Example 1.

[0064] Comparative Example 1 A hydrogel sealing agent comprises the following raw materials in percentage by weight: 4% acryloyl cyclodextrin, 12% acrylamide, 8% cellulose aqueous dispersion, 0.4% cross-linking agent (N, N'-methylenebisacrylamide), 1% initiator (potassium persulfate), and the balance water; the total amount of each component is 100%.

[0065] The preparation method of acryloyl cyclodextrin is the same as that in Example 1.

[0066] The preparation method of the cellulose aqueous dispersion comprises the following steps: fully dispersing a nanocellulose fibril gel (available from Nanjing Tianlu Nanotechnology Co., Ltd., with a fiber diameter of 3-5 nm, a fiber length of 500-1000 nm, and a solid content of 2 wt%) in deionized water. The content of the nanocellulose fibrils is the same as that in Example 1.

[0067] The preparation method of the above hydrogel sealing agent is the same as that of Example 1.

[0068] Comparative Example 2 A hydrogel sealing agent, the raw material composition is as described in Example 1, except that: the tannic acid grafted polysaccharide aqueous dispersion is omitted, and the omitted component is replaced with the same amount of water.

[0069] The preparation method of the above hydrogel sealing agent is the same as that of Example 1.

[0070] Comparative Example 3 A hydrogel sealing agent, the raw material composition is as described in Example 1, except that: acryloyl cyclodextrin is replaced by acrylamide of the same mass.

[0071] The preparation method of the above hydrogel sealing agent is the same as that of Example 1.

[0072] Test example The sealing agents obtained in the examples and comparative examples were tested as follows.

[0073] Test 1, tensile properties test The packing agent was placed at 80℃ for 6h, and then made into dumbbell-shaped test strips with a length of 30mm, a width of 5mm, and a thickness of 2mm. The tensile mechanical properties of the gel were tested using an electronic universal testing machine, and the tensile rate was set to 5mm / min. The stress-strain values ​​of the packing agent samples were recorded when they were stretched. The tensile properties results are shown in Table 1.

[0074] Test 2: Packer compression resistance test The packing agent was placed at 80℃ for 6h, and then made into a cylinder with a bottom diameter of 20mm and a height of 10mm. The gel compression mechanical properties were tested using an electronic universal testing machine. The compression speed was set to 3mm / min, and the stress-strain value of the sample was recorded when it was compressed. The compression resistance results are shown in Table 1.

[0075] Table 1 Toughness and compression performance test of packing agent

[0076] As can be seen from Table 1, when the content of acrylamide used in Example 2 is reduced, the number of monomers participating in the polymerization is reduced; this means that the length of the generated polymer chain will become shorter; in the gel formation process, the polymer chain is a key part of building the gel network structure, and the reduction in chain length will cause the skeleton of the gel network to become sparse; in addition, the number of polymer chains is reduced, and the contact points with the tannic acid-grafted cellulose are also reduced accordingly, which will weaken the mutual entanglement and interaction between the polymer and cellulose in the gel system, resulting in a decrease in the mechanical properties of the gel.

[0077] N, N'-methylenebisacrylamide (MBA) is an efficient crosslinking agent that can form a tight crosslinking network between polymer chains, thereby improving the strength of the gel. The crosslinking agent polyethylene glycol diacrylate used in Example 3 contains a longer polyethylene glycol segment, which introduces more flexible segments during the crosslinking process, resulting in a relatively low crosslinking density and an increase in the distance between crosslinking points, thereby reducing the strength of the gel.

[0078] The nanocrystals used in Example 4 have a more regular crystal structure, and their size and shape are relatively uniform. They are more evenly dispersed in the gel, but do not form a long-range interwoven network like fibrils, resulting in a decrease in tensile length and compressive strength.

[0079] In Example 5, the dosage of acrylamide was increased, and in Examples 6 and 7, the dosage of tannic acid grafted cellulose dispersion, crosslinking agent and initiator were changed, resulting in changes in the gel structure formed by the sealing agent and changes in the mechanical properties.

[0080] In Example 8, acrylamide is replaced by acrylic acid, in Example 9, the mass ratio of acryloyl chloride and β-cyclodextrin is adjusted, in Example 10, acryloyl chloride is replaced by methacryloyl chloride of the same mass, in Example 11, the polysaccharide substance is replaced by lignin, and in Example 12, the mass ratio of tannic acid and nanocellulose fibrils is adjusted. The structure of the obtained gel will change accordingly, thereby affecting its mechanical properties.

[0081] Comparative Example 1 does not use tannic acid grafting. When tannic acid is grafted on the cellulose surface, it acts as a "bridge" to promote the interaction between cellulose and other gel components (such as grafted β-cyclodextrin and acrylamide polymer). Due to the lack of the "bridge" effect of tannic acid in Comparative Example 1, the interaction between cellulose and other gel components is weakened, and the structural stability and dispersibility of the gel network are affected, thereby reducing the overall strength of the gel.

[0082] In Comparative Example 2, the tannic acid-grafted polysaccharide is replaced with water. When it is replaced with water, the number of structural supports and cross-linking points in the gel is reduced, causing the gel network to become looser.

[0083] Comparative Example 3 is acrylamide. When acryloyl cyclodextrin is replaced by acrylamide, the cross-linking points and structure in the gel network change, and the effective cross-linking points decrease.

[0084] Test 3, Rheological properties of packing agent The sealing agent was placed at 80 °C for 6 h, and then made into a circular sheet with a bottom diameter of 30 mm and a height of 3 mm. The rheological properties of the sealing agent were tested using a HAAKEMARS 60 rheometer. The test conditions for the storage modulus (G') and loss modulus (G") were 1.0% constant strain, the oscillation scanning frequency was set to 1 Hz, and the angular frequency range was set to 0.01-100 rad·s -1 , and record the storage modulus (G') and loss modulus (G") of the above-mentioned sealing agents. The rheological results (G' and G") at 1 Hz are shown in Figure 3.

[0085] Table 2 Rheological properties of the packing agent

[0086] As can be seen from Table 2, changes in the amount of acrylamide or raw materials, changes in the type of cross-linking agent, changes in the type of polysaccharide substances, changes in the type of polymerization monomers, changes in the preparation conditions of acryloyl cyclodextrin, and changes in the preparation conditions of tannic acid grafted polysaccharide aqueous dispersions will all lead to changes in the structure of the resulting gel, thereby hardening the rheological properties of the resulting gel.

[0087] In Comparative Example 1, tannic acid grafting was not used, and the connectivity between cellulose and other structures was reduced, and the elastic modulus decreased. In Comparative Example 2, the tannic acid grafted polysaccharide was replaced with water. Because the gel network lost the structural reinforcement provided by the tannic acid grafted cellulose, the connection and support between the molecular chains became weaker, and the elastic modulus decreased. In Comparative Example 3, acryloyl cyclodextrin was replaced with acrylamide of the same mass. The special interaction brought by the cyclodextrin structure was lost in the gel network, the interaction between the molecular chains was reduced, and the elastic modulus decreased.

[0088] Test 4, pH degradation ability The sealing agent prepared by the method of Example 1 was placed at 80°C for 6 hours to form a gel. 100g of the colloid was taken, 30g of a 5wt% sodium hydroxide aqueous solution was added, and the mixture was allowed to stand for 10 hours. The rheological properties of the above mixture were tested using a HAAKE MARS 60 rheometer, where the test conditions for the storage modulus (G') were 1.0% constant strain, the oscillation scanning frequency was set to 1Hz, and the angular frequency range was set to 0.01-100rad·s -1 The storage modulus G' of the mixed solution was recorded. The rheological results (G' at 1 Hz) are shown in Table 3.

[0089] Table 3 pH degradation ability data

[0090] It can be seen from the data in Table 3 that after alkali treatment, the strength is greatly reduced due to the dissociation of hydrogen bonds, and the gel is basically degraded, which shows that the packing agent of the present invention has pH degradation ability after gelation and can achieve unblocking after plugging.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A supramolecular hydrogel sealing agent constructed by host-guest interaction, characterized in that: The raw material composition comprises the following mass percentages: 12-36% of copolymerization monomer, 6-10% of tannic acid grafted polysaccharide aqueous dispersion, 0.5-1.5% of initiator, 0.3-0.6% of crosslinking agent, and the balance of water; the total amount of each component is 100%; The copolymerization monomer is a combination of acryloyl cyclodextrin and a double bond-containing monomer; the double bond-containing monomer is one of acrylamide, acrylic acid, methacrylic acid, sodium acrylate, N-isopropylacrylamide, hexadecyl dimethyl allyl ammonium chloride or N-hydroxyethyl acrylamide; The preparation method of acryloyl cyclodextrin comprises the steps of: dissolving cyclodextrin and sodium hydroxide in deionized water, adding acryloyl chloride or methacryloyl chloride, reacting, filtering, precipitating and drying to obtain acryloyl cyclodextrin; The preparation method of tannic acid grafted polysaccharide aqueous dispersion comprises the following steps: fully dispersing polysaccharide material in deionized water and adjusting the pH to 8.0; adding tannic acid and obtaining tannic acid grafted polysaccharide aqueous dispersion through reaction; the polysaccharide material is one or a combination of two or more of cellulose, starch, lignin, xanthan gum, chitosan, guar gum or sodium alginate.

2. The supramolecular hydrogel sealing agent constructed by host-guest interaction according to claim 1, characterized in that: The supramolecular hydrogel sealing agent constructed by host-guest interaction comprises the following raw materials in percentage by weight: 16% copolymerization monomer, 8% tannic acid grafted polysaccharide aqueous dispersion, 1% initiator, 0.4% crosslinking agent, and the balance is water; the total amount of each component is 100%.

3. The supramolecular hydrogel sealing agent constructed by host-guest interaction according to claim 1, characterized in that: The method for preparing acryloyl cyclodextrin includes one or more of the following conditions: i. The cyclodextrin is selected from one or a combination of two or more of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin; ii. The mass ratio of cyclodextrin to sodium hydroxide is 1-4:5.84; the mass ratio of cyclodextrin to deionized water is 1:50-150; the mass ratio of acryloyl chloride or methacryloyl chloride to cyclodextrin is 0.5-2.2:2; iii. The reaction temperature is 40-60°C; the reaction time is 6-12h; the reaction is carried out under inert gas protection and stirring conditions; the inert gas is nitrogen or argon.

4. The supramolecular hydrogel sealing agent constructed by host-guest interaction according to claim 1, characterized in that: The mass ratio of acryloyl cyclodextrin to the double bond-containing monomer is 1:2-8.

5. The supramolecular hydrogel sealing agent constructed by host-guest interaction according to claim 1, characterized in that: The method for preparing the tannic acid grafted polysaccharide aqueous dispersion includes one or more of the following conditions: i. The polysaccharide material is cellulose, and the cellulose is selected from nanocellulose fibrils, cellulose nanocrystals or carboxymethyl cellulose; ii. The mass ratio of polysaccharide to deionized water is 1:20-30; iii. Use 0.01 mol / L sodium hydroxide aqueous solution or 0.01 mol / L HCl aqueous solution to adjust the pH to 8.0; iv. The mass ratio of polysaccharide to tannic acid is 3:5-8; v. The reaction temperature is room temperature and the reaction time is 12-24 hours; the reaction is carried out under stirring conditions.

6. The supramolecular hydrogel sealing agent constructed by host-guest interaction according to claim 1, characterized in that: The initiator is selected from one or a combination of two or more of azobisisobutyronitrile, azobisisoheptanenitrile, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, potassium persulfate, ammonium persulfate, dicumyl peroxide or di-tert-butyl peroxide.

7. The supramolecular hydrogel sealing agent constructed by host-guest interaction according to claim 1, characterized in that: The crosslinking agent is selected from one or a combination of two or more of dimethyl sulfide, N,N'-methylenebisacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, ethylene oxide, propylene oxide, phenolic resin, formaldehyde, polyethylene glycol diacrylate or boric acid.

8. The method for preparing the supramolecular hydrogel sealing agent constructed by host-guest interaction according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: fully dispersing copolymerization monomers, tannic acid grafted polysaccharide aqueous dispersion, initiator and crosslinking agent in water at room temperature.

9. Use of the supramolecular hydrogel sealing agent constructed by host-guest interaction according to any one of claims 1 to 7 in the process of crude oil production and drilling.

10. The use according to claim 9, characterized in that: The application method comprises the following steps: during drilling, a supramolecular hydrogel sealing agent constructed by host-guest interaction is injected into the formation, and gelled at the formation temperature to seal the crude oil reservoir; after drilling, an alkaline solution is injected for unblocking; the alkaline solution is a sodium hydroxide aqueous solution with a mass concentration of 5-15%, and the mass ratio of the alkaline solution to the supramolecular hydrogel sealing agent is 30-60:1; the crude oil is heavy oil, and the heavy oil is crude oil with a viscosity greater than or equal to 1000 mPa·s at 50°C.

Citation Information

Patent Citations

  • Supramolecular polymer gel plugging agent based on multiple hydrogen bonds and preparation method thereof

    CN116120905A

  • CM-beta-CD loaded tannic acid polyacrylamide type dual-network antibacterial hydrogel

    CN114404646A

  • Supramolecular gel plugging agent for fractured formation as well as preparation method and application of supramolecular gel plugging agent

    CN114507515A

  • Organic-inorganic composite material system for preventing / controlling CO2 stratum leakage as well as preparation method and application of organic-inorganic composite material system

    CN117384455A

  • Supramolecular polymer gel packer as well as preparation method and application thereof

    CN118388719A

Cited By

  • Polymer gel packing system with cross-linked network structure and application thereof

    CN120082339A

  • A polymer gel isolation system with a cross-linked network structure and its application

    CN120082339B

  • Lithium battery pole piece processing method and lithium battery preparation method thereof

    CN120784288A

  • Composite nitrogen foam profile control and flooding system and profile control and flooding method

    CN121160314A